Application of the Original Agroecological Survey and Indicator System tool (OASIS) to organic and conventional farms in Belgium, France, and Italy - Alexander Wezel; Alexander Wezel; Paola Migliorini; Paola Migliorini; Anna Brumer; Tommaso Gaifami; Tommaso Gaifami; Angelica Marchetti; Geoffrey Floymont; Garance Guizard; Elsa Michel; Marie-Alix Renaud; et al. (Frontiers in Agronomy)
European agriculture faces major challenges in adapting and transforming current farming and food systems to become more sustainable. Agroecology is one transition pathway. However, what is lacking is assessing this transition with adequate tools and methodology. Here, we present the Original Agroecological Survey and Indicator System (OASIS) tool and apply it to farms in Belgium, France, and Italy as an illustration of its functionalities. In total, 53 conventional and organic farmers of three farming systems [crop production (CP); livestock production (LP), and mixed crop–livestock production (CLP)] were interviewed and data were collected for a large range of indicators (scoring from 1 to 5) across five dimensions: agroecological farming practices, economic viability, socio-political aspects, environment and biodiversity, and resilience. Overall, organic farms had slightly higher scores compared to conventional farms for the five dimensions. However, for the adoption of different agroecological practices, a clear difference was found, often with clearly higher scores for organic farms. There were also similar differences regarding most biodiversity and environment indicators and indicators for revenue and income sources. Farms that had higher overall farm scores also obtained a generally significantly higher mark for economic viability. Farmers described many parameters among the socio-political aspects dimension criteria, including several constraints that resulted in lower scores. Contrasting results for different criteria were found for the dimension of resilience, with some farms scoring higher for autonomy and independence from inputs and market, while others scored lower. As an operational result, overall, the OASIS tool proved applicable and useful in assessing agroecology at the farm level and some links beyond. However, further development could improve the tool.